Educators' perspectives on facilitating computer-assisted speech intervention in early childhood settings. (October 2017) - Crowe, Kathryn; Cumming, Tamara; McCormack, Jane; Baker, Elise; McLeod, Sharynne; Wren, Yvonne; Roulstone, Sue; Masso, Sarah
Early childhood educators are frequently called on to support preschool-aged children with speech sound disorders and to engage these children in activities that target their speech production. This study explored factors that acted as facilitators and/or barriers to the provision of computer-based support for children with speech sound disorders (SSD) in early childhood centres. Participants were 23 early childhood educators at 13 centres who participated in the Sound Start Study, a randomized controlled trial that examined the effectiveness of the Phoneme Factory Sound Sorter ® (PFSS) computer program (Wren and Roulstone, 2013). Following the trial, participants completed a telephone interview discussing their experiences implementing the program. Transcripts from the interviews were analysed and three categories emerged as factors that influenced the provision of support: (1) personal factors that related to the children (engagement with PFSS, inclusion/exclusion experience), peers, and educators (service provision, educator engagement, support of child PFSS use); (2) environmental factors that related to policies and philosophies (child-centred practice, technology), the physical environment (inclusion/exclusion), and logistics (time, technology); and (3) program factors that related specifically to PFSS (program format, specific games, game duration). In order to best meet the needs of children, parents, educators, and clinicians, these factors need to be taken into consideration in the provision of speech and language therapy services in early childhood centres.